Hubungan Antara Usia dan Pendidikan dengan Persiapan Laktasi Pada Ibu Hamil Di Klinik Asih Waluyo Jati, Bantul - Dewi Anggraeni, Fatimah; Rahmawati, Dechoni (INVOLUSI: Jurnal Ilmu Kebidanan, 2022)
Background: To reduce child morbidity and mortality, the United National Fund (UNICEF) and the World Health Organization (WHO) recommend that children only be breastfed using breast milk (ASI) for at least 6 months and complementary foods given to breast milk after the baby is older than 6 months. The coverage of infants who were exclusively breastfed in Bantul Regency in 2019 was 78.96%, where the coverage of breastfeeding in Bantul Regency had not yet reached the national target of 80% (Bantul Health Office, 2020). Objective: The relationship between age and education with lactation preparation in pregnant women at the Asih Waluyo Jati clinic, Bantul, YogyakartaResearch Methodology: This type of research is analytic observational with a cross-sectional approach. The location of this research is Asih Walyo Jati Clinic, Bantul, with a sample of 21 respondents and the sampling technique used is purposive random sampling. The data analysis technique used in this research is to use the chi square test. The results: There is a relationship between age and lactation preparation with a p value of n, p value of 0.004 and an ood ratio of 1.875. There is a relationship between age and lactation preparation with a p value of n, p value of 0.02 and an ood ratio of 2.75.